KEBIJAKAN PENANGANAN AKSI UNJUK RASA YANG DILAKUKAN OLEH PENGUNGSI DARI LUAR NEGERI - Adi Sujatno; Tiyar Cahya Kusuma; Eros Shidqy Putra (Universitas Labuhanbatu, 2023)
Indonesia is not a country that is obliged to accept and take care of refugees from abroad because it did not participate in ratifying the 1951 Convention on the Status of Refugees and the 1967 Protocol on the Status of Refugees. Nevertheless, Indonesia continues to receive refugees every year. It was recorded that until August 2022, the number of refugees in Indonesia was 12,993 people, consisting of 9,713 refugees and 3,280 asylum seekers. Although Indonesia is not obliged to accept refugees, the Indonesian government still accommodates and cares for them because it is based on aspects of Human Rights (HAM). One of the most prominent problems in the handling of refugees from abroad is the rampant demonstrations carried out by the refugees to immediately be placed in third countries. In tackling the problems of the refugees, Presidential Regulation No. 125 of 2016 has been issued regarding the Handling of Refugees from Overseas. However, the Presidential Regulation does not clearly regulate the handling of demonstrations carried out by refugees because basically the refugees are not Indonesian citizens and there is no law that regulates the problem of demonstrations carried out by these refugees.Keywords : Policy, Demonstration, Refugee